PROSPECTS FOR SOCIO-ECONOMIC DEVELOPMENT OF THE ECONOMY OF KOSHKOPIR DISTRICT - Sobirov Javoxir Xayrulla oʻgʻli; Karimova Shahnoza Ahmed qizi; Matnazarova Malohat Islambayevna (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the work done and planned measures for the socio-economic development of the economy of Koshkopir district using the available land and labor resources. It is also based on the views of the authors of the article on the socio-economic development of the district.